Morfologia, crescimento e produtividade de cultivares modernas e antigas de batata em diferentes ambientes - Eschemback, Vlandiney (2014)
The objective of this study was to evaluate the morphology, growth and yield of new and old potato cultivars and to compare national and European cultivars, in contrasting locations. Both experiments were conducted in the field in 2013, one from January to April in Guarapuava - PR and another from August to November in Brasilia. In both experiments treatments consisted of 6 cultivars: Agata, Monalisa and Bintje (cultivars of European origin), BRS Clara, Catucha and Baronesa (cultivars of Brazilian origin), representing modern, intermediate and old cultivars, respectively. The seeds were planted by hand, using spacing between rows of 0.80 m in both locations and spacing between plants of 0.25 m (Guarapuava) and 0.30 m (Brasília). Each experimental plot consisted of 6 rows of 18 plants arranged in a complete randomized block design with 4 replications totaling 24 plots at both locations. Morphological characteristics and growth of cultivars at 39, 54, 69 and 84 days after planting (DAP), as well as their final yield were analysed. It was observed that modern cultivars Agata in Guarapuava and Clara and Agata in Brasília, had earlier onset of tuber formation with high mass, high tuber bulking rate and high leaf area index (LAI). For Monalisa, it was observed low initial tuber bulking rate at both locations, showing significant increase in mass of tubers after 69 DAP. Catucha showed higher values for main stem length in both Guarapuava and Brasília, and high LAI during this period. Baronesa and Bintje showed the highest number of secondary stems in Brasilia, with low difference on other measured parameters compared to the other cultivars. The modern cultivars, with the exception of Catucha, were more productive than older cultivars both in Guarapuava and Brasilia and it was not found significant differences in yield between European and Brazilian cultivars. Therefore, it is concluded that modern cultivars have fast initial growth in both Guarapuava and in Brasília resulting in higher yield potential in both places and Brazilian cultivars have potential for increasing their national market share.